Systemic inflammatory markers in neck pain: A systematic review with meta‐analysis. (20th July 2020) - Farrell, Scott F.; de Zoete, Rutger M. J.; Cabot, Peter J.; Sterling, Michele
Abstract: Background and Objective: Mechanisms underpinning symptoms in non‐traumatic neck pain (NTNP) and whiplash‐associated disorder (WAD) are not comprehensively understood. There is emerging evidence of systemic inflammation in musculoskeletal pain conditions, including neck and back pain. The aim of this systematic review was to determine if raised blood inflammatory markers are associated with neck pain. Databases and Data Treatment: MEDLINE, EMBASE, Cochrane Library, CINAHL and Web of Science databases were searched. Two independent reviewers identified studies for inclusion and extracted data. Meta‐analysis was performed by random effects model to calculate standard mean differences (SMDs). Risk of bias of individual studies was assessed using the Newcastle–Ottawa Scale. Overall quality of evidence from meta‐analysis was assessed by Grades of Recommendation, Assessment, Development and Evaluation approach. Results: In total, 10 studies were included comprising 706 participants. Three studies provided data for acute WAD, two for chronic WAD, four for chronic NTNP and one for chronic mixed WAD and NTNP. Meta‐analysis indicated increased interleukin 1β (SMD: 0.84 [95% CI 0.24, 1.44], p  = .01, I 2  = 59%) and tumour necrosis factor α (SMD: 0.59 [0.09, 1.09], p  = .02, I 2  = 45%) in chronic neck pain compared to controls, but no increase in monocyte chemoattractant protein‐1. Some inflammatory markers were associated with clinical variables (including pain intensity and disability). Quality of evidence was mostly low due to small samples and high heterogeneity. Conclusions: Findings imply that raised blood inflammatory markers are present in chronic neck pain, which may represent an ongoing inflammatory process in this population. Significance: This systematic review advances our understanding of neck pain pathophysiology by demonstrating the presence of systemic inflammation in chronic neck pain, in the form of raised IL‐1β and TNFα. Further, numerous inflammatory markers were associated with clinical variables, including pain intensity, disability and hyperalgesia. These findings imply that systemic inflammation may contribute to mechanisms underlying neck pain.